MicroRNA miR-214 Inhibits Snakehead Vesiculovirus Replication by Promoting IFN-α Expression via Targeting Host Adenosine 5′-Monophosphate-Activated Protein Kinase - Zhang, Chi; Feng, Shuangshuang; Zhang, Wenting; Chen, Nan; Hegazy, Abeer M.; Chen, Wenjie; Liu, Xueqin; Zhao, Lijuan; Li, Jun; Lin, Li; Tu, Jiagang (Frontiers in Immunology, 2017)
Background: Snakehead vesiculovirus (SHVV), a new rhabdovirus isolated from diseased hybrid snakehead, has emerged as an important pathogen during the past few years in China with great economical losses in snakehead fish cultures. However, little is known about the mechanism of its pathogenicity. MicroRNAs (miRNAs) are small noncoding RNAs that posttranscriptionally modulate gene expression and have been indicated to regulate almost all cellular processes. Our previous study has revealed that miR-214 was downregulated upon SHVV infection. Results: The overexpression of miR-214 in striped snakehead (SSN-1) cells inhibited SHVV replication and promoted IFN-α expression, while miR-214 inhibitor facilitated SHVV replication and reduced IFN-α expression. These findings suggested that miR-214 negatively regulated SHVV replication probably through positively regulating IFN-α expression. Further investigation revealed that AMP-activated protein kinase (AMPK) was a target gene of miR-214. Knockdown of AMPK by siRNA inhibited SHVV replication and promoted IFN-α expression, suggesting that cellular AMPK positively regulated SHVV replication and negatively regulated IFN-α expression. Moreover, we found that siAMPK-mediated inhibition of SHVV replication could be partially restored by miR-214 inhibitor, indicating that miR-214 inhibited SHVV replication at least partially via targeting AMPK. Conclusion: The findings of this study complemented our early study, and provide insights for the mechanism of SHVV pathogenicity. SHVV infection downregulated miR-214, and in turn, the downregulated miR-214 increased the expression of its target gene AMPK, which promoted SHVV replication via reducing IFN-α expression. It can therefore assume that cellular circumstance with low level of miR-214 is beneficial for SHVV replication and that SHVV evades host antiviral innate immunity through decreasing IFN-α expression via regulating cellular miR-214 expression.